Economic and analytical diagnostics in the financial activity management system of a modern health care institution - Melnyk, Alla; Zhukevych, Svitlana (Herald of Economics, 2023)
Introduction. The concept of the development of the system of financial support in the field of health care outlines the need to introduce a new financial mechanism, which provides for the provision of a sufficient level of managerial and financial autonomy to medical institutions.The change in the nature of financial relations imposes new requirements on the management of financial activities in health care institutions. The functional component of managerial activity is economic and analytical diagnostics, the application of which will ensure the adaptability of financial management methods and models to modern realities and the integration of the finances of health care institutions into the system of competitive market relations.Purpose. The purpose of the study is the development of theoretical provisions of economic-analytical diagnostics and the development of methodological approaches for its application in the management of financial activities of health care institutions in the conditions of transformational changes.Methods. Achieving the set goal is achieved by using general scientific, special and empirical methods of learning processes and phenomena. The methods of analysis and synthesis, comparison, and generalization are used to understand economic and analytical diagnostics in the management system; scientific abstraction, structural-logical and tabular methods for determining the methodology of economic-analytical diagnostics in modern health care institutions.Results. It has been proven that the mechanism of management activity of state institutions with elements of entrepreneurial structures, which are currently medical institutions, requires the use of modern economic and analytical methods and diagnostic models and their adaptation to the specifics of the activities of health care institutions. The analysis of the main approaches of scientists to the definition and understanding of economic-analytical diagnostics as a functional component of managing the financial activities of a health care institution was carried out, and it was determined that the essence of economic-analytical diagnostics of health care institutions should be the system of management activities regarding decision-making on the investment of financial and other resources to provide quality services that will ensure the efficiency and competitiveness of the health care institution.At the same time, the main tasks are defined: analysis of the financial activity of medical institutions, assessment of production capacities and resource base and means of their improvement, which will ensure the financial and economic stability and stability of medical institutions with the approval of market positions and/or exit from the crisis state.It is substantiated that the indicators of the efficiency and stability of the functioning of the health care institution should form an optimal management model of an expedient and justified system of financing and provision of financial resources and the efficiency of their spending.The use of integral methods and models that combine internal and external factors of the functioning of economic entities is proposed to carry out economic and analytical diagnostics and determine the capabilities of health care institutions. The main approaches to the SWOT analysis methodology with the possibility of its adaptation and application in the management of health care institutions were studied.Discussion. In order to carry out economic and analytical diagnostics regarding the determination of the capabilities of health care institutions, including financial ones, in addition to SWOT analysis, it is advisable to use other integral methods and models that combine internal and external factors of the functioning of economic entities in the field of medicine, which may be the subject of further research.